Quiet Quitting dan Kesehatan Mental di tempat kerja: Systematic Literature Review - Baiq Elok Mandalika; Nurul Isnaini; Faisal Adnan Reza; Ahmad Zarkasy (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
The phenomenon of quiet quitting reflects the restriction of employee engagement as a response to increasing workplace pressures in the globalization and post-pandemic era. This study aims to systematicall analyze the characteristic of key fingdings regarding qiet quitting and its impact in employee mental health in the workplace. The method employed is a Systematic Literature Review (SLR) following PRISMA 2020 guidelines and CASP quality assessment search was conducted across five major databases using Rayyan AI software, resulting in 35 relevant juournals published between 2020 and 2025. The results indicate that quiet quitting is an adaptive strategy to protect mental health from excessive workloads and unsupportive work environments. The most dominant impacts found include high turnover intention, decreased productivity, and increased stress and burnout. In conclusion, quiet quitting serves as a vital indicator of organizational health that requires proactive interventions such as enchanced psychological safety and well- being programs to maintain employee mental health and retention.